Fungal planet description sheets: 1550-1613 - Crous, Pieter Willem (2023)
Novel species of fungi described in this study include those from various countries as follows: Argentina, Neocamarosporium halophilum in leaf spots of Atriplex undulata. Australia, Aschersonia merianiae on scale insect (Coccoidea), Curvularia huamulaniae isolated from air, Hevansia mainiae on dead spider, Ophiocordyceps poecilometigena on Poecilometis sp. Bolivia, Lecanora menthoides on sandstone, in open semi-desert montane areas, Sticta monlueckiorum corticolous in a forest, Trichonectria epimegalosporae on apothecia of corticolous Megalospora sulphurata var. sulphurata, Trichonectria puncteliae on the thallus of Punctelia borreri. Brazil, Catenomargaritapseudocercosporicola (incl. Catenomargarita gen. nov.) hyperparasitic on Pseudocercospora fijiensis on leaves of Musa acuminata, Tulasnella restingae on protocorms and roots of Epidendrum fulgens. Bulgaria, Anthracoidea umbrosae on Carex spp. Croatia, Hymenoscyphus radicis from surface-sterilised, asymptomatic roots of Microthlaspierraticum, Orbilia multiserpentina on wood of decorticated branches of Quercus pubescens. France, Calosporella punctatispora on dead corticated twigs of Acer opalus. French West Indies (Martinique), Eutypella lechatii on deadcorticated palm stem. Germany, Arrhenia alcalinophila on loamy soil. Iceland, Cistella blauvikensis on dead grass (Poaceae). India, Fulvifomes maritimus on living Peltophorum pterocarpum, Fulvifomes natarajanii on dead wood of Prosopis juliflora, Fulvifomes subazonatus on trunk of Azadirachta indica, Macrolepiota bharadwajii on moist soil near the forest, Narcissea delicata on decaying elephant dung, Paramyrothecium indicum on living leaves of Hibiscus hispidissimus, Trichoglossum syamviswanathii on moist soil near the base of a bamboo plantation. Iran,Vacuiphoma astragalicola from stem canker of Astragalus sarcocolla. Malaysia, Neoeriomycopsis fissistigmae (incl. Neoeriomycopsidaceae fam. nov.) on leaf spots on flower Fissistigma sp. Namibia, Exophiala lichenicola lichenicolous on Acarospora cf. luederitzensis. Netherlands, Entoloma occultatum on soil, Extremus caricis on dead leaves of Carex sp., Inocybe pseudomytiliodora on loamy soil. Norway, Inocybe guldeniae on calcareous soil, Inocybe rupestroides on gravelly soil. Pakistan, Hymenagaricus brunneodiscus on soil. Philippines, Ophiocordyceps philippinensis parasitic on Asilus sp. Poland, Hawksworthiomyces ciconiae isolated from Ciconia ciconia nest, Plectosphaerella vigrensis from leaf spots on Impatiens noli-tangere, Xenoramularia epitaxicola from sooty mould community on Taxus baccata. Portugal, Inocybe dagamae on clay soil. Saudi Arabia, Diaporthe jazanensis on branches of Coffea arabica. South Africa, Alternaria moraeae on dead leaves of Moraea sp., Bonitomyces buffelskloofinus (incl. Bonitomyces gen. nov.) on dead twigs of unknown tree, Constrictochalara koukolii on living leavesof Itea rhamnoides colonised by a Meliola sp., Cylindromonium lichenophilum on Parmelina tiliacea, Gamszarella buffelskloofina (incl. Gamszarella gen. nov.) on dead insect, Isthmosporiella africana (incl. Isthmosporiella gen. nov.) on dead twigs of unknown tree, Nothoeucasphaeria buffelskloofina (incl. Nothoeucasphaeria gen. nov.), on dead twigs of unknown tree, Nothomicrothyrium beaucarneae (incl. Nothomicrothyrium gen. nov.) on dead leaves of Beaucarnea stricta, Paramycosphaerella proteae on living leaves of Protea caffra, Querciphoma foliicola onleaf litter, Rachicladosporium conostomii on dead twigs of Conostomium natalense var. glabrum, Rhamphoriopsis synnematosa on dead twig of unknown tree, Waltergamsia mpumalanga on dead leaves of unknown tree. Spain, Amanita fulvogrisea on limestone soil, in mixed forest, Amanita herculis in open Quercus forest, Vuilleminia beltraniae on Cistus symphytifolius. Sweden, Pachyella pulchella on decaying wood on sand-silt riverbank. Thailand, Deniquelata cassiae on dead stem of Cassia fistula, Stomiopeltis thailandica on dead twigs of Magnolia champaca. Ukraine, Circinaria podoliana on natural limestone outcrops, Neonematogonum carpinicola (incl. Neonematogonumgen. nov.) on dead branches of Carpinus betulus. USA, Exophiala wilsonii water from cooling tower, Hygrophorus aesculeticola on soil in mixed forest, and Neocelosporium aereum from air in a house attic. Morphological and culture characteristics are supported by DNA barcodes.